A new perspective of frozen shoulder pathology; the interplay between the brain and the immune system - Navarro-Ledesma, Santiago; Hamed-Hamed, Dina; Pruimboom, Leo (Frontiers in Physiology, 2024)
Frozen shoulder (FS), also known as adhesive capsulitis of the shoulder (FS), is a fibrotic inflammatory process of unknown etiology whose main symptoms are pain, stiffness and the loss of joint mobility. These symptoms may be associated with pathologies such as diabetes, Dupuytren’s syndrome and the prevalence of today’s sedentary lifestyle. This literature review provides an overview of the epidemiology and pathogenesis of this pathology, as well as the mechanisms of lowgrade chronic inflammation and infection, insulin resistance, and omics-science associated with it. We also propose a new hypothesis related to the possibility that the GABAergic system could play a decisive role in the development of frozen shoulder and that therefore diabetes type 1, endocrinological autoimmune disorders and frozen shoulder are connected by the same pathophysiological mechanisms. If that is true, the combined presence of psycho-emotional stress factors and pathogenic immune challenges could be the main causes of frozen shoulder syndrome. Finally, we propose a series of possible intervention strategies based on a multifactorial etiological and mechanistic concept.